Anatomy & Physiology for Health Professions - Jonathan Bubb (Cengage Learning, 2021)
MindTap for Anatomy & Physiology for Health Professions, 1st Edition, helps you learn on your terms. INSTANT ACCESS IN YOUR POCKET. Take advantage of the Cengage Mobile App to learn on your terms. Read or listen to textbooks and study with the aid of instructor notifications, flashcards and practice quizzes. MINDTAP HELPS YOU CREATE YOUR OWN POTENTIAL. GEAR UP FOR ULTIMATE SUCCESS. Track your scores and stay motivated toward your goals. Whether you have more work to do or are ahead of the curve, you'll know where you need to focus your efforts. And the MindTap Green Dot will charge your confidence along the way. MINDTAP HELPS YOU OWN YOUR PROGRESS. MAKE YOUR TEXTBOOK YOURS. No one knows what works for you better than you. Highlight key text, add notes and create custom flashcards. When it's time to study, everything you've flagged or noted can be gathered into a guide you can organize. ACCESS TO 3D MODELS AND ANIMATIONS View important anatomic structures, physiologic processes, and pathologies as interactive 3D models. Zoom, rotate, and click on structures to enhance your understanding of anatomy & physiology. BUILT IN CLINICAL CORRELATIONS Explore the pathologic conditions affecting the organs and organ systems you are studying. This integration will give you the added edge when encountering these and similar conditions in your healthcare profession. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.